(untitled) - Coddington, Dean C. (San Francisco, 2001)
Learn to can better meet the needs of the new consumer-driven marketplace. Strategies for the New Health Care Marketplace--written by a team of acclaimed experts--examines the factors changing today's health care system: the growth in demand for services, the increasing influence of consumers on how services are provided, and the dramatic new advances in treatment made possible by technology.
Keywords: Medical care--Forecasting,Medical innovations,Medical economics